Letter - West, R.
1949-04-29 038-0008-002 the position. As you will remember about 4000 Basque children came over to England originally - Only 295 remain, all except 3 are working and look after themselves. I heard that the centre (39 Victoria St) is considerably less in consequence and it was felt that we could not continue to appeal for funds for the maintenance and repatriation of these young people when so few of them need maintenance grants and so few return to Spain - Some of those who have returned during past 12 months or so even offered to pay own fares. We are probably closing down by end of year. Probably some after care committee without central offices may [continue] function - In regard to adult Spaniards the position is rather different more & more adults are coming to England from France (some escape from Spain every week) These need advice - and it was felt that the TUC might like to have something to say re best way of continuing this side of work. 292/946/38/8(II)